ANALISIS CUSTOMER RELATIONSHIP MANAGEMENT STUDI KASUS DI PERUSAHAAN OUT-OF HOME CV XYZ - , Ronny Tua Siregar, Dr. Iin Mayasari, MM., M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The purpose of this thesis is to examine how a company in outdoor advertising maintains its clientsâ satisfaction. This research use case study method at CV. XYZ, a company in outdoor advertising industry (out-of-home). This research focus on how the company implement customer relationship management (CRM) for its two major customers: PT. ABC and PT. DEF. The result of this study shows that CV. XYZ already has worked flow based on outdoor media location points and has strategy in maintaining relationship with customers. However, there are several weaknesses in how the company implements customer relationship management. CV. XYZ has not determined each functions and tasks in detail for every personnel in the company, which often results job delay in one division holding back the settlement for overall job. CV. XYZ has ProVis system, which contains information that the company could use to build good CRM. Nevertheless, all this time the interaction between company and its clients has not been documented well. The company also has not have systematic method to measure clientsâ satisfaction. In average, the time the company needs to settle jobs order from clients is quite good. But sometimes the jobs settlement needs longer time due to constraints in the field related to coordination with local society and also local government. In addition, there is no formal mechanism for clients to file complaints.